Comunidade de aves aquáticas e suas interações em sistemas límnicos do sudeste brasileiro - Branco, Magno Botelho Castelo (Universidade Federal de São Carlos, 2008)
Aquatic birds do interact in many ways with freshwater ecosystems. Birds can be considered the most important dispersers of freshwater algae between water bodies. Moreover, birds also can contribute to nutrient loading in freshwater lakes and reservoirs. In this paper the ecto and endozoochoric dispersal potential of freshwater algae by waterbirds was acessed. The places of study were the Monjolinho reservoir, in São Carlos municipality (SP), and Tropeiros lake, in Piumhi municipality (MG). Also studied was the contribution to nutrient loading by two colonies of Bubulcus ibis, the cattle egret, in two freshwater bodies: Tropeiros lake and Iembó reservoir, locate at Parque Itaipu, São Carlos municipality. By means of culture inoculation with material obtained from washing the body of the birds, it was observed that these species of birds are potential dispersers of phytoplanktonic algae and can carry up to 22 species of algae attached to feathers per individual (ectozoochory). A minor number of species of algae was also observed in cultures inoculated with material derived from faeces of birds, featuring a potential case of endozoochoric transport potential. Regarding the nutrient loading by colony of cattle egrets, was detected a change both in the content of organic matter in the sediment located in areas where the birds sleep as well as greater eutrophication of water in these regions. It was also observed a trend to higher density of biomass in banks of aquatic macrophytes used for night rest, with a consequent increase in the density of organisms associated with aquatic macrophytes. However, no significant differences were observed in the benthic fauna, when comparing the samples of sediment obtained in both points located in the rest areas as in nonrest areas, but it was found that these colonies contribute significantly to the nutrient loading in these systems.
Keywords: Limnologia; Ave aquática; Diversidade biológica; Interações biológicas; Dispersão de algas; Biodiversidade em águas doces; Aquatic birds; Freshwater biodiversity; Biological interactions; Algae dispersion; CIENCIAS BIOLOGICAS::ECOLOGIA